Sequencing type material resolves the identity and distribution of the generitype Lithophyllum incrustans, and related European species L. hibernicum and L. bathyporum (Corallinales, Rhodophyta). Issue 4 (24th July 2015) - Hernandez‐Kantun, Jazmin J.; Rindi, Fabio; Adey, Walter H.; Heesch, Svenja; Peña, Viviana; Le Gall, Line; Gabrielson, Paul W.; Lane, C.
<x xml:space="preserve">Abstract</x> DNA sequences from type material in the nongeniculate coralline genus Lithophyllum were used to unambiguously link some European species names to field‐collected specimens, thus providing a great advance over morpho‐anatomical identifi‐cation. In particular, sequence comparisons of rbcL, COI and psbA genes from field‐collected specimens allowed the following conclusion: the generitype species, L. incrustans, occurs mostly as subtidal rhodoliths and crusts on both Atlantic and Mediterranean coasts, and not as the common, NE Atlantic, epilithic, intertidal crust reported in the literature. The heterotypic type material of L. hibernicum was narrowed to one rhodolith belonging in Lithophyllum. As well as occurring as a subtidal rhodolith, L. hibernicum is a common, epilithic and epizoic crust in the intertidal zone from Ireland south to Mediterranean France. A set of four features distinguished L. incrustans from L. hibernicum, including epithallial cell diameter, pore canal shape of sporangial conceptacles and sporangium height and diameter. An rbcL sequence of the lectotype of Lithophyllum bathyporum, which was recently proposed to accommodate Atlantic intertidal collections of L. incrustans, corresponded to a distinct taxon hitherto known only from Brittany as the subtidal, bisporangial, lectotype, but also occurs intertidally in Atlantic Spain. Specimens from Ireland and France morpho‐anatomically identified as L. fasciculatum and a specimen from Cornwall likewise identified as L. duckerae were resolved as L. incrustans and L. hibernicum, respectively.